Analysis of poetic personality- “SAROJINI NAIDU”, “Nightingale of India, a poet and politician” - DURGA, DR. SHIVA; MEHROTRA, DR. VIVEK (The journal of contemporary issues in business and government, 2021)
Sarojini Naidu is well acknowledged as the Title of “Nightingale of India” was a high-achieving student, prominent independence struggle activist of India and also a sonnetist. She was the first lady Indian President of our country, she was a lady prominent figure and she was the first Governor of the state Uttar Pradesh, was a dynamic personality as a patriot and politician too, a person who writes polemics and was an effective inspiration for all of well known women’s in the country India and as a whole in the entire world, Mrs. Sarojini Naidu’s eponym is at the peak level. Amongst the other famous personalities, even though she was genuinely one of the extraordinary personalities of the entire earth. She was among the most famous personalities of the century numbered as 20th, her arrival to the earth as a strong personality is acknowledged by a special day known as “Women’s Day”. Paper is focused on the remarkable benchmark the area of poetry. Her poetic sense is focused with a remarkable bank of words which are so ethnic to sing with real feelings. “Bul Bul-e-Hind” was published in the year 1905 and this was an initialization of her poetic aspect. This paper focuses on the aspects of The Pardah Nashin, The Village Song, Lotus and The bird of time.